ROTARY FURNACES FOR THERMAL PROCESSING AND DRYING OF POLYDISPERSE MATERIALS - S. L. Rovin; L. E. Rovin; O. M. Valitskaja (Литьë и металлургия)
It is shown that rotary furnaces and drying ovens are a perspective type of furnaces, allowing to solve a number of problems in conditions of flexible production and strong resources economy